Effects of postdepositional processing on nitrogen isotopes of nitrate in the Greenland Ice Sheet Project 2 ice core. Issue 13 (7th July 2015) - Geng, Lei; Zatko, Maria C.; Alexander, Becky; Fudge, T. J.; Schauer, Andrew J.; Murray, Lee T.; Mickley, Loretta J.
Abstract Records of ice core nitrate and its isotopes hold the potential to assess past atmospheric conditions regarding NOx and oxidant levels. However, relating such records to past atmospheric conditions requires a site‐specific understanding of the postdepositional processing of snow nitrate. We report δ15N(NO3−) records from the Greenland Ice Sheet Project 2 (GISP2) ice core over major climate transitions. Model calculations and comparison with records of parameters influencing UV‐driven postdepositional processing of snow nitrate suggest that the observed variability in GISP2 δ15N(NO3−) over major climate transitions is primarily driven by changes in the degree of postdepositional loss of snow nitrate. Estimates of the fractional loss of snow nitrate is (16–23)% in the Holocene and (45–53)% in the glacial period, suggesting a (41 ± 32)% lower nitrate depositional flux to Greenland during the glacial period relative to the Holocene.